1990
DOI: 10.1136/gut.31.8.875
|View full text |Cite
|
Sign up to set email alerts
|

Relation between flow-pressure-diameter studies in experimental stenosis of rabbit and human small bowel.

Abstract: Patients with inflammatory and ischaemic bowel diseases seem to tolerate narrowing of the gut lumen to a critical degree of stenosis without obstructive symptoms. To determine the physical factors involved in bowel occlusion, we created an experimental model using New Zealand rabbits in acute experiments under general anaesthesia. At operation a loop of small bowel was isolated and canulated, proximally for perfusion and pressure recording and distally to monitor flow. Having established the physiological pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…Results of a study 44 in rabbits indicate that gastrointestinal flow depends on intraluminal pressure, luminal diameter, and the viscoelastic properties of intestinal contents. Coordinated intestinal contractions generate pressure gradients to overcome the resistance to flow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of a study 44 in rabbits indicate that gastrointestinal flow depends on intraluminal pressure, luminal diameter, and the viscoelastic properties of intestinal contents. Coordinated intestinal contractions generate pressure gradients to overcome the resistance to flow.…”
Section: Discussionmentioning
confidence: 99%
“…Coordinated intestinal contractions generate pressure gradients to overcome the resistance to flow. 44 The luminal diameter and rheologic properties of RDC contents are major factors that determine the resistance to flow. 42 Decreased intestinal diameter and increased viscosity of the contents increase resistance to flow up to a point where flow is interrupted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports, however, show that stapled anastomoses have a higher bursting pressure and a better blood supply than anastomoses made with sutures [9, 10, 11, 12]. Furthermore, an edematous anastomosis narrows the intestinal lumen, and the intraluminal pressure rises proximal to an intestinal stricture [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Arterial remodeling limits change in wall shear stress [7]. Animal models suggested that the minimal diameter and luminal narrowing were related to pressure and flow [14] and that the relation between luminal narrowing and renal blood flow could be not linear [15].…”
Section: Interpretation Of Datamentioning
confidence: 99%